Determinants of the Quality of the Maluku Provincial Government Financial Statements - Mis Fertyno Situmeang; Semy Pesireron (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study empirically examines the effects of Regional Government Information System (SIPD) implementation and information technology utilization on the quality of the Maluku Provincial Government financial statements. A quantitative explanatory survey was conducted among 150 financial management officials selected purposively from 30 regional government agencies. Data were collected using a five-point Likert-scale questionnaire and analyzed with descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression using SPSS. The findings indicate that SIPD implementation has a positive and significant effect on local government financial statement quality (β = 0.37; t = 7.54; p < 0.001). Information technology utilization also has a positive and significant effect (β = 0.37; t = 3.62; p < 0.001). These results confirm that integrated financial information systems and effective technology use support the accuracy, reliability, relevance, and timeliness of public financial reporting. The study implies that the Maluku Provincial Government should strengthen user competence, network reliability, system integration, technical assistance, and data backup procedures to optimize SIPD-based financial reporting and public accountability.